ICT Pedagogy in Higher Education: A Constructivist Approach - Jha, Anila (Journal of Training and Development, 2017)
Information and communication technology (ICT) has been an integral part of pedagogy in educational institutions in general and higher education in particular. My focus in this paper is to see how ICT plays a role in constructing knowledge and improving learning in the higher educational institutions. The arguments are based on the review of existing ICT related literature, and in- depth interviews with few ICT pedagogy and social constructivist related educationists. So, the method applied is qualitative. First, ICT plays a role of a means to an end in the sense that it carries messages with higher level of accuracy. Second, it makes the interactions among the target group ‘living’ and creates the environment for effective learning. Third, ICT links the performers (teachers and students) in the learning groups cognitively and affectively to transform the unit of learning among the learners. This means that ICT plays a vital role in the part of the learners in which they are liberated from their teachers’ dominance.